(untitled) (Mustansiria Dental Journal, 2018)
This study evaluated the transverse strength of polymerized acrylic resin after immersion in sodium hypochlorite (NaOCl) for 20 minute, 3times a day for 15 days. 40 rectangular specimens were prepared from heat polymerized acrylic resin; 20 specimens were immersed in 0.5℅ NaOCl as experimental group and 20 specimens were immersed in distilled water as control group. The transverse strength was measured using a 3 –point bending test in a universal testing machine. The study showed that there was no statistically significant differences (p>0.05) between groups. It may be concluded that immersion in NaOCl solution did not influence the transverse strength of heat polymerized acrylic resin.